Information Dissemination during COVID-19 Pandemic among Postgraduate Allied Health Sciences Students in Pakistan - Misbah Jabeen, Muhammad Shahjahan, Ghulam Farid, (Pakistan Journal of Medical & Health Sciences, 2023)
Purpose: This study determines the information dissemination during the Covid-19 pandemic and examine the impact on the educational activity of postgraduate students in Allied Health Sciences institute in Pakistan. Methodology: Present quantitative study is based on survey method that was carried out to assess the effectiveness of information dissemination during Covid-19 pandemic among postgraduate allied health science students in different universities in Lahore Pakistan. Finding: The response rate of the study remained 80%. Majority of users, about 69.5% (n=66) students responded that they did not have challenges in information dissemination during Covid-19, while 30.5% (n=29) students respond that the information was poor. Respondents of the study found highly satisfied with the efficiency of library on providing e-services during Covid-19 (P-Value = 0.487). usability of libraries in information dissemination in which 74 (78%) responded that libraries provide access to reliable and trustworthy Covid-19 pandemic information via different media. 75(79%) students are agreed on providing awareness sensitization on how to restrain the spread of Covid-19 pandemic, online and offline services provided by libraries to allied health science students, challenges faced by libraries in the dissemination of information 77 (81%) Students respond that there is inadequate skills and knowledge of utilizing the Internet resources and services. The recommendations of the study might be beneficial to enhance the effectiveness of resources and services of universities libraries. Keywords: University Library; Library Website; Library User; Covid-19 Pandemic; Information Dissemination; Information Technology; Post Graduate Allied Health Science, Students.